Translation Procedures and Equivalence in Children Bilingual Short Story - Eka Putri Septarani (ITScience (Information Technology and Science), 2022)
This study was aimed at finding the procedures and meaning equivalence of translation. This study focuses on Indonesian- English translation found in a collection of animal short stories for children. The research method used is descriptive qualitative. Newmark’s theory of translation procedures was used to analyze the translation procedure in the story. Another theory that was used is Nida’s theory of meaning equivalence. The first step in analyzing the data started by reading the entire short story and marking the difference between the Indonesian and English words. Each representative theory then analyzed the data. After being analyzed, the result is displayed in tables and explanations. Based on the study that has been done, it was found that there were 13 out of 16 translation procedures. The most commonly used translation found in this study is Literal Translation with 40 occurrences, and the least procedure used in this study was Descriptive Equivalent with 2 occurrences. In addition, this study also found Nida's Formal and Dynamic Equivalent in terms of meaning equivalence. The most commonly used meaning equivalence found in this study was Dynamic Equivalent. This study showed that procedures of translation and meaning equivalence are deeply tied since the selection of translation procedures will determine the category of its equivalence.